Предмет: Математика,
автор: vanya5555
8(4-3y)-(7-2y)=-(6+3y)+8(y-2) решить уравнение с обьяснением и проверкой
Ответы
Автор ответа:
0
8(4 - 3у) - (7 - 2у) = - (6 + 3у) + 8(у - 2)
32 - 24у - 7 + 2у = - 6 - 3у + 8у - 16
- 24у + 2у + 3у - 8у = - 6 - 16 - 32 + 7
- 27у = - 47
у = - 47 : (- 27)
у = 47/27
у = 1 20/27
32 - 24у - 7 + 2у = - 6 - 3у + 8у - 16
- 24у + 2у + 3у - 8у = - 6 - 16 - 32 + 7
- 27у = - 47
у = - 47 : (- 27)
у = 47/27
у = 1 20/27
Похожие вопросы
Предмет: География,
автор: cergeyykoloc0v
Предмет: Математика,
автор: ksenii2425
Предмет: Математика,
автор: sekotovsasa5
Предмет: Геометрия,
автор: Baatareyka
Предмет: Математика,
автор: Дан29